Profit Motive, Stakeholder Needs and Economic Dimension of Corporate Social Responsibility: Analysis on The Moderating Role of Religiosity - Aminu Ahmadu Hamidu; Md. Harashid Haron; Azlan Amran (Indonesian Journal of Sustainability Accounting and Management, 2018)
Economic dimension of corporate social responsibility (CSR) represent the main aim of establishing all forms of business organizations. The outcome from all transactions translate into the process of attaining continuity, growth, satisfactory returns, maximization of shareholders wealth and provision of goods and services to the community. Achievement of all these goals depends on how managers are able to perfect the profit motive objective and satisfy the needs of all stakeholders. A total of 164 respondents who are the managers responsible for decision making on all corporate social responsibility activities were engaged in answering the questionnaire for this study. The managers were representing different sub sectors of the Nigerian financial sector. A statistical analysis on the data was done by using the partial least square approach (PLS-SEM). Results from the analysis revealed that both profit motive and stakeholder needs are positively related with the economic dimension of CSR. Religiosity of managers is also positively related with ability of managers to attain economic responsibilities they were employed to achieve. With the role of religiosity as a significant moderating factor managers are expected to align CSR activities with accepted religious values that instills hard work, trust and assistance to stakeholders to fulfill the overall economic dimension of corporate social responsibility.